Rabbit Polyclonal Antibodies Against the Calcium-Dependent Conformation of Factor IX and Their Application in Solid Phase Immunoradiometric Assays - Poort, S R; Linden, I K van der; Es, C Krommenhoek-van; Briët, E; Bertina, R M (Thrombosis and Haemostasis, 1986)
Two subpopulations of antibodies were isolated from rabbit polyclonal antiserum directed against human factor IX: one against the Ca(II)-dependent conformation of factor IX and one against the Ca(II)-independent conformation of factor IX. The two subpopulations were used for the development of immunoradiometric assays (IRMA’s) for factor IX: Ca(II)Ag and factor IX: NonCa(II)Ag respectively. Ranges for the concentration of factor IX:Ca(II)Ag and factor IX: NonCa(II)Ag were established in plasmas of healthy volunteers, patients treated with oral anticoagulants and hemophilia B patients. In the group of patients using oral anticoagulant therapy a progressively reduced ratio of factor IX:Ca(II)Ag to factor IX: NonCa(II)Ag was observed with increasing intensity of oral anticoagulant treatment. Variant factor IX molecules from hemophilia B patients . (CRM-, CRMRed and CRM+) with a defective Ca(II) binding or defective conformational transition induced by Ca(II) binding, were identified. These defects are absent in variant factor IX molecules from one hemophilia Bm patient and from patients with hemophilia B Leyden.
Keywords: Factor IX antibodies; Calcium dependency; Oral anticoagulation; Hemophilia B